PERAMALAN KUNJUNGAN WISATAWAN DAN DAYA DUKUNG BEE JAY BAKAU RESORT PROBOLINGGO - Mochammad Fattah; Tiwi Nurjannati Utami; Dwi Sofiati (Jurnal Analisis Kebijakan Kehutanan, 2020)
City of Probolinggo offers nine main tourist attractions, such as Environmental Study Park (TWSL), Probolinggo Museum, Dr. Moh. Saleh Museum, Red Church, Tri Dharma Temple, Coastal Fishing Port, Bayuangga Swimming Pool, Olimpic Swimming Pool, and Bee Jay Bakau Resort (BJBR). One of the main destinations with ecotourism concept in Probolinggo city is BJBR. It is important to handle a research about forecasting the tourism visits and carrying capacity to support decision making in BJBR management. The purpose of this study is to analyze the forecasting of the foreign and domestic tourists visits at BJBR and analyze the carrying capacity. Quantitative methods using ARIMA and Winter are used in this study. This study also uses carrying capacity area analysis to analyze the carrying capacity of BJBR. The result shows that BJBR Probolinggo provides varied tourist attractions that affect the number of visits. The best forecasting is Winter method because the forecasting error is smaller than ARIMA method, which is, the average on visiting are 14,866tourist/month or 496 tourists/day. Meanwhile, the carrying capacity of the BJBR is 1,110 tourists/day. The management should consider tourist visit forecasting and the carrying capacity.